1973
DOI: 10.4141/cjas73-024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Frequency of Feeding on Energy Metabolism and Body Composition of Young Pigs

Abstract: and 340 kcal ME/W.'-n" daily; and feeding frequency: two and five times daily)'One metabolism experiment was conducted during the 3rd wk of the 37-day feeding experiment. Subcutaneous adipose tissue slices taken immediately after electrocution of 24 pigs were used to determine the rate of lipogenesis as indicated by the metabolism of glucose-U-'+C. Frequency of feeding had no effect on the digestible energy, ME, and N8,,, value of the diet or the efficiency of utilization of ME for maintenance. However, freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…These results were similar to those of Sharma et al, (1973), who revealed that frequency of feeding influenced energy utilization. In that study, pigs fed multiple times had greater maintenance requirements but also were more efficient converters of the ME available above the maintenance requirement for tissue deposition.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results were similar to those of Sharma et al, (1973), who revealed that frequency of feeding influenced energy utilization. In that study, pigs fed multiple times had greater maintenance requirements but also were more efficient converters of the ME available above the maintenance requirement for tissue deposition.…”
Section: Discussionsupporting
confidence: 91%
“…This result may have been due to improved nutrient digestibility (de Haer and de Vries, 1993b) and a change in basal metabolism (Sharma et al, 1973) associated with an increase in feeding frequency. This result may have been due to improved nutrient digestibility (de Haer and de Vries, 1993b) and a change in basal metabolism (Sharma et al, 1973) associated with an increase in feeding frequency.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the above-mentioned studies, the amount of daily feed was not adjusted between treatments, so that the response in terms of fat gain might be partly related to the total amount of feed consumed in each groups (Friend and Cunningham, 1964) rather than to the frequency of in- gested food. When reasoning at the same feed intake, the lack of changes observed herein with daily meal frequency for perirenal fat proportion and lipid contents in adipose tissues is in agreement with another study in growing pigs showing that lipid content in the empty body did not vary when pigs were fed 2 vs. 5 meals a day (Sharma et al, 1973). Similarly, body composition was unchanged in rats fed 2 vs. 10 to 12 meals at 80% of their usual food intake (Hill et al, 1988).…”
Section: Less Frequent Meals Promote Weight Gain and Feed Efficiency supporting
confidence: 91%
“…The detrimental effect of frequent daily meals on pig's efficiency is not in accordance with our initial assumption that consuming more meals per day could be at a metabolic advantage. The opposite response observed herein could be associated with effects of meal frequency at the whole-animal level, such as greater maintenance requirements for pigs receiving a high number of meals compared with those fed twice daily (Sharma et al, 1973), greater energy needs for digestion when very frequent meals are fed due to the thermic effect of feed, or differences in activity and energy expenditure between those pigs. In support of this latter aspect, pigs (Friend and Cunningham, 1964;Sharma et al, 1973) and rats (Leveille and O'Hea, 1967) fed once or twice daily were generally less sensitive to the excitation associated with the distribution of feed than animals receiving multiple small meals.…”
Section: Less Frequent Meals Promote Weight Gain and Feed Efficiency mentioning
confidence: 56%
See 1 more Smart Citation